2023
DOI: 10.1097/bot.0000000000002614
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach and Dislocation Risk After Hemiarthroplasty in Geriatric Patients With Femoral Neck Fracture With and Without Cognitive Impairments—Does Cognitive Impairment Influence Dislocation Risk?

Abstract: Objectives: To determine whether there is an association between surgical approach and dislocation risk in patients with cognitive impairment compared with those without cognitive impairment treated with hemiarthroplasty for femoral neck fracture. Design: Retrospective study. Setting: Large, multicenter health system. Patients/Participants: One thousand four hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Unfortunately, dislocation of the HA lacks an ICD-10 diagnosis code, why it is difficult to find the precise number of people affected. The existing literature is unclear of the dislocation rates of the hip HA, ranging from 1 -12% (1)(2)(3)(4)(5)(6)(7)(8). Many studies describing prevalence, incidence or incidence rate base their dislocation rate on patients treated at their facility or insurance data.…”
Section: Dislocation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, dislocation of the HA lacks an ICD-10 diagnosis code, why it is difficult to find the precise number of people affected. The existing literature is unclear of the dislocation rates of the hip HA, ranging from 1 -12% (1)(2)(3)(4)(5)(6)(7)(8). Many studies describing prevalence, incidence or incidence rate base their dislocation rate on patients treated at their facility or insurance data.…”
Section: Dislocation Ratementioning
confidence: 99%
“…Knowledge of reasons for dislocation of the hip HA would help surgeons choose, or opt out, on the implant when the patient is deemed too high-risk for dislocation, or we might be able to warn the patients' of the possible risks and push them to be more careful. Thus, there are several studies suggesting some risk factors for dislocation of the hip HA, such as surgical approach (1,5,6), cognitive impairment (2,(5)(6)(7)(8), prosthesis type(4) and uncemented vs cemented implant (3). However, such studies often contradict each other, and there is a lack of conclusive evidence and the hierarchy of the proposed risk factors are unknown.…”
Section: Risk Factors For Dislocationmentioning
confidence: 99%
“…Recent prospective studies have emphasized the long known unfavorable prognostic role exerted by cognitive impairment after hip fracture in older people. Impaired cognition has been significantly associated with high mortality rates, 1 , 2 increased risk of recurrent fractures and prosthetic hip dislocations, 3 , 4 blunted ability to function in activities of daily living, 5 , 6 impaired mobility, 7 low likelihood of discharge home and reduced number of days alive and at home, a combined patient-centered outcome measure. 8 , 9 The recent results are in agreement with a lot of previous original studies and various systematic reviews: on the whole, the wider literature has consistently reported poor outcomes in cognitively impaired subjects with a fragility fracture of the hip.…”
mentioning
confidence: 99%